Upregulation of PTEN in glioma cells by cord blood mesenchymal stem cells inhibits migration via downregulation of the PI3K/Akt pathway. - Venkata Ramesh Dasari (Public Library of Science (PLoS), 2010)
Background PTEN (phosphatase and tensin homologue deleted on chromosome ten) is a tumor suppressor gene implicated in a wide variety of human cancers, including glioblastoma. PTEN is a major negative regulator of the PI3K/Akt signaling pathway. Most human gliomas show high levels of activated Akt, whereas less than half of these tumors carry PTEN mutations or homozygous deletions. The unique ability of mesenchymal stem cells to track down tumor cells makes them as potential therapeutic agents. Based on this capability, new therapeutic approaches have been developed using mesenchymal stem cells to cure glioblastoma. However, molecular mechanisms of interactions between glioma cells and stem cells are still unknown. Methodology/principal findings In order to study the mechanisms by which migration of glioma cells can be inhibited by the upregulation of the PTEN gene, we studied two glioma cell lines (SNB19 and U251) and two glioma xenograft cell lines (4910 and 5310) alone and in co-culture with human umbilical cord blood-derived mesenchymal stem cells (hUCBSC). Co-cultures of glioma cells showed increased expression of PTEN as evaluated by immunofluorescence and immunoblotting assays. Upregulation of PTEN gene is correlated with the downregulation of many genes including Akt, JUN, MAPK14, PDK2, PI3K, PTK2, RAS and RAF1 as revealed by cDNA microarray analysis. These results have been confirmed by reverse-transcription based PCR analysis of PTEN and Akt genes. Upregulation of PTEN resulted in the inhibition of migration capability of glioma cells under in vitro conditions. Also, wound healing capability of glioma cells was significantly inhibited in co-culture with hUCBSC. Under in vivo conditions, intracranial tumor growth was inhibited by hUCBSC in nude mice. Further, hUCBSC upregulated PTEN and decreased the levels of XIAP and Akt, which are responsible for the inhibition of tumor growth in the mouse brain. Conclusions/significance Our studies indicated that upregulation of PTEN by hUCBSC in glioma cells and in the nude mice tumors downregulated Akt and PI3K signaling pathway molecules. This resulted in the inhibition of migration as well as wound healing property of the glioma cells. Taken together, our results suggest hUCBSC as a therapeutic agent in treating malignant gliomas.